Identification of Cassava (Manihot esculenta Crantz.) miRNAs Targeting the Genome of Cassava Mosaic Virus - Anjana, Haridas; T., Makeshkumar; J., Sreekumar (JOURNAL OF ROOT CROPS, 2021)
Cassava Mosaic Disease caused by cassava mosaic virus is one of the most devastating crop diseases affecting cassava cultivation. Bioinformatics approach was applied to search cassava (Manihot esculenta Crantz.) miRNAs that targeted the cassava mosaic virus genome. Nucleotide sequences representing the genome of cassava mosaic virus were screened against a set of mature cassava miRNAs. Efficacy of cassava miRNAs against putative viral mRNA targets was analysed based on complementarity of miRNA-mRNA target pairing. This study revealed 14 cassava miRNA families to have putative targets in the cassava mosaic virus with nearly perfect complementarity. These miRNAs when artificially designed may have the potential to confer effective resistance against cassava mosaic disease infection in transformed cassava